2010
DOI: 10.1002/clc.20692
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Study of Pulmonary Embolism and High‐density Lipoprotein Cholesterol

Abstract: Background: It is currently thought that pulmonary embolism and deep vein thrombosis are different manifestations of the same pathological process of venous thromboembolism. Venous thromboembolism has a negative correlation with high-density lipoprotein cholesterol. Hypothesis: Pulmonary embolism has a negative correlation with the level of high-density lipoprotein cholesterol. Methods: A total of 90 patients with pulmonary embolism, diagnosed and treated at a single center, were retrospectively analyzed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…53 ). Several studies have shown that HDL-C levels correlate inversely with different pathological modes of thrombosis ( 54,55 ). HDL can oppose LDL induction of platelet aggregation, serotonin release, and thromboxane B2 production ( 56 ), and it can block ox-LDL inhibition of nitric oxide synthase ( 57 ).…”
Section: Hdl Functional Diversity Matches Its Proteomic Diversitymentioning
confidence: 99%
“…53 ). Several studies have shown that HDL-C levels correlate inversely with different pathological modes of thrombosis ( 54,55 ). HDL can oppose LDL induction of platelet aggregation, serotonin release, and thromboxane B2 production ( 56 ), and it can block ox-LDL inhibition of nitric oxide synthase ( 57 ).…”
Section: Hdl Functional Diversity Matches Its Proteomic Diversitymentioning
confidence: 99%
“…High-density lipoprotein cholesterol-C may reduce the risk of atherosclerotic lesions by the reverse cholesterol transport, anti-inflammatory and antioxidant effects, and attenuation of endothelial dysfunctions. 3 In previous studies, it has been shown that serum HDL-C levels are significantly low in PE 11,22,23 and elevated serum HDL-C levels might decrease the risk of PE in postmenapausal women. 12 A recent study, by Wang et al showed that pulmonary arterial trunk embolism is negatively correlated with the level of HDL-C. 23 In contrast, other previous studies found no association between HDL-C and PE.…”
Section: Discussionmentioning
confidence: 95%
“…3 In previous studies, it has been shown that serum HDL-C levels are significantly low in PE 11,22,23 and elevated serum HDL-C levels might decrease the risk of PE in postmenapausal women. 12 A recent study, by Wang et al showed that pulmonary arterial trunk embolism is negatively correlated with the level of HDL-C. 23 In contrast, other previous studies found no association between HDL-C and PE. 3,16,4 Chamberlain et al found low HDL-C does not appear to be an important VTE risk factor.…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al also reported that pulmonary arterial trunk embolism was negatively correlated with the level of HDL cholesterol (11). The risk factors for VTE recurrence during anticoagulation include immobilization, cancer, and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 96%